Performance based concrete quality assessment with gas permeability testing on site - Ptacek, Lisa; Strauss, Alfred; Grba, Damjan; Sattler, Fabian; Macha, Makrini; Kosta, Angeliki; Marchtrenker, Stefan; Boisits, Philip; Manninger, Tanja; Krispel, Stefan; Kleiser, Michael; Hausenberger, Rainer; et al. (Frontiers in Built Environment, 2024)
In terms of sustainability and durability, performance-based design is becoming increasingly important for the quality assessment of concrete structures. Up to now, prescriptive approaches for concrete composition and processing and the determination of concrete strength on cast samples have primarily been used as quality assurance. As this does not take into account the quality and pore structure of the as-built concrete cover, which has a significant influence on durability as a protective zone against penetrating media, the conventional approach to quality control is not representative for this zone. In particular, the permeability of the concrete cover, which is largely dependent on the pore structure, is responsible for the ability of aggressive substances from the environment to ingress into the concrete and, depending on its quality, determines damage processes in the reinforced concrete, such as carbonation. For this reason, investigations to gas permeability on real structures are presented here, which include the possibilities and limitations of measuring and evaluating gas permeability as a durability indicator. Long-term observation was carried out on concrete walls of a motorway construction site, from a young concrete age of 14 days to a higher age of max. 800 days, in order to determine changes in the material structure of the surface area and to analyse their influence on the gas permeability. The concrete walls were treated in advance during hydration up to an age of 7 days with different curing times and types in order to simulate good, medium and poor concrete surfaces. Clear differences in the quality of the concrete cover could already be determined by means of gas permeability. The influence of the surface structure, the effect of the environment and the long-term development of the concrete structure on the permeability are also addressed in this work.